The cone penetrometer test applied to the determination of the undrained shear strength of fine-grained soils - Escalaya Advíncula, Miriam Rosanna (2023)
The behavior of soft fine-grained soils is considered one of the most complex and problematic, from a geotechnical point of view. For this reason, knowledge of its strength and deformability parameters is important and fundamental. In this paper, a review of the available literature is carried out about the use of fall-cone test in determining the undrained shear strength of these soils, the necessary calibrations and the main advances in the determination of the cone factor K. Fall-Cone este is widely used to obtain the liquid limit of soils, and due to the ease of use it becomes a quick and economical alternative to obtain the undrained shear strength of soft clay soils.